2021
DOI: 10.1002/cctc.202100293
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Conversion of Syngas to Higher Alcohols over a CuCoAl|t‐ZrO2 Multifunctional Catalyst

Abstract: Selective synthesis of higher alcohols from syngas is promising but remains challenging owing to the low stability and selectivity towards higher alcohols. Here we introduce a CuCoAl j t-ZrO 2 (t denotes tetragonal crystal phase) multifunctional catalyst that can achieve an alcohol selectivity of 64.8 % with 79.6 % C 2 + OH, and a total selectivity of alcohols and olefins to 81.7 %. The proper proximity was tuned to increase selectivity towards alcohols and decrease the selectivity towards hydrocarbons. The lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 70 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…One type of multifunctional catalyst contains a modified FTS component and methanol synthesis component such as CoMn|CuZnAlZr, CuCoAl|t-ZrO 2 , and CuCoAl|ZnO/ZrO 2 . ,,, Lin et al developed a multifunctional catalyst composed of CoMn and CuZnAlZr that offered 58.1% (CO 2 -free) oxygenate selectivity with more than 92 wt % being C 2+ OH at a CO conversion of 29.0% under 250 °C and H 2 /CO = 1 . The total selectivity of value-added chemicals including oxygenates and olefins reached up to 80.6 wt %.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…One type of multifunctional catalyst contains a modified FTS component and methanol synthesis component such as CoMn|CuZnAlZr, CuCoAl|t-ZrO 2 , and CuCoAl|ZnO/ZrO 2 . ,,, Lin et al developed a multifunctional catalyst composed of CoMn and CuZnAlZr that offered 58.1% (CO 2 -free) oxygenate selectivity with more than 92 wt % being C 2+ OH at a CO conversion of 29.0% under 250 °C and H 2 /CO = 1 . The total selectivity of value-added chemicals including oxygenates and olefins reached up to 80.6 wt %.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…It was demonstrated that the increase of surface coverage of valid oxygenate-containing species (i.e., CO*, CH x O*) can kinetically promote the CO insertion rate. Fang et al reported that CuCoAl|t-ZrO 2 and CuCoAl|ZnO/ZrO 2 exhibited a similar promotional effect for HAS. , CuCoAl|t-ZrO 2 with strong basic sites lowered the surface [H*]/[C*] ratio and inhibited hydrogenation of alkyl species, thus benefiting CO insertion and achieving ∼51% C 2+ OH selectivity (CO 2 -free) at 12.7% CO conversion. A similar strategy can be expanded to Mo-based HAS catalysts such as ZnCrAlO x |KNiMoS-MMO-5, which afforded 60.4% total alcohol selectivity with a more than ∼72.7% C 2+ OH fraction at a CO conversion of 9.8% …”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of catalysts are applied to ethanol production from syngas: Rhbased, [5,6] Mo-based [7,8] and Cu-based catalysts (including modified methanol catalysts and modified Fischer-Tropsch catalysts). [9,10] Cu-based catalysts have attracted substantial interest owing to their mild reaction conditions and low price. [11][12][13] Various great efforts have been taken to clarify the mechanism of ethanol synthesis and the nature of active sites on Cu-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among the routes for the ethanol production, catalytic transformation of syngas (a mixture of H 2 and CO) to ethanol has received much attention due to its wide range of raw materials and simple nonpetroleum process. Three types of catalysts are applied to ethanol production from syngas: Rh‐based, [5,6] Mo‐based [7,8] and Cu‐based catalysts (including modified methanol catalysts and modified Fischer‐Tropsch catalysts) [9,10] . Cu‐based catalysts have attracted substantial interest owing to their mild reaction conditions and low price [11–13] …”
Section: Introductionmentioning
confidence: 99%